2020
DOI: 10.1371/journal.pone.0226735
|View full text |Cite
|
Sign up to set email alerts
|

Complex patterns of cell growth in the placenta in normal pregnancy and as adaptations to maternal diet restriction

Abstract: The major milestones in mouse placental development are well described, but our understanding is limited to how the placenta can adapt to damage or changes in the environment. By using stereology and expression of cell cycle markers, we found that the placenta grows under normal conditions not just by hyperplasia of trophoblast cells but also through extensive polyploidy and cell hypertrophy. In response to feeding a low protein diet to mothers prior to and during pregnancy, to mimic chronic malnutrition, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…Our work also reveals that the capacity for placental adaptation to support fetal growth is sex-dependent. This phenomenon is not limited to maternal alcohol intake or protein insufficiency but is commonly reported in studies investigating other prenatal stressors including maternal dietary restriction, maternal asthma, preeclampsia, and gestational diabetes [52][53][54][55][56][57]. Although well-documented, the underlying basis for these sexdependent placental responses remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…Our work also reveals that the capacity for placental adaptation to support fetal growth is sex-dependent. This phenomenon is not limited to maternal alcohol intake or protein insufficiency but is commonly reported in studies investigating other prenatal stressors including maternal dietary restriction, maternal asthma, preeclampsia, and gestational diabetes [52][53][54][55][56][57]. Although well-documented, the underlying basis for these sexdependent placental responses remains unclear.…”
Section: Discussionmentioning
confidence: 89%
“…One (clusters 6, 10, and 24) expressed markers of pericytes (e.g. Acta2 ) and several growth factors including Wnt5b and Pdgfrb that are critical for development and maintenance of vascular populations ( Eaton et al, 2020 ). The other (clusters 15 and 19) expressed Gata4 , Kit, and Pdpn.…”
Section: Resultsmentioning
confidence: 99%
“…The mouse placenta is comprised of three distinct zones; the maternally derived decidua, and the conceptus-derived junctional and labyrinth zones. The labyrinth zone consist of two layers of multinucleated syncytiotrophoblast (SynT) cells resulting in a large surface area for nutrient and gas exchange between mother and fetus [ 27 ]. Blinded histological analysis of placental sections showed that the area of labyrinth zone was significantly reduced in mRUPP compared to Sham ( Fig.…”
Section: Resultsmentioning
confidence: 99%